2017
DOI: 10.1021/acs.jpclett.7b00413
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Light-Induced and Intrinsic Nonadiabatic Phenomena in Diatomics

Abstract: Nonadiabatic effects arise due to avoided crossings or conical intersections that are either present naturally in field-free space or induced by a classical laser field in a molecule. Recently, it was demonstrated that nonadiabatic effects in diatomics can also be created in an optical cavity. Here, the quantized radiation field mixes the nuclear and electronic degrees of freedom. We show the equivalence of using the cavity's quantized field and the classical laser field as usually done for molecules. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 48 publications
3
52
1
Order By: Relevance
“…We show in this work that the molecular cavity photodynamics of LiF may drastically change upon the quantum field present in the cavity. In addition, contrary to previous statements [14,15] we believe that our results indicate that the fully quantum nature of the radiation is expressed in features that cannot be reproduced whatsoever using a classical light. THEORY We assume an optical cavity with a single mode confined radiation with frequency ω c .…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We show in this work that the molecular cavity photodynamics of LiF may drastically change upon the quantum field present in the cavity. In addition, contrary to previous statements [14,15] we believe that our results indicate that the fully quantum nature of the radiation is expressed in features that cannot be reproduced whatsoever using a classical light. THEORY We assume an optical cavity with a single mode confined radiation with frequency ω c .…”
Section: Introductioncontrasting
confidence: 99%
“…x Although the cavity photodynamics of NaI has been recently treated in Ref. [10,11,14,15], we would like to provide a more comprehensive account of the inner workings of the underlying mechanisms that give shape to the time-dependent populations and the dissociation yields in the similar molecule LiF. We want to address the problem assuming that the cavity can be filled with different types of quantum states of radiation, namely, Fock states, coherent states and squeezed coherent states, which are known to have very different properties.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario resembles a one-dimensional (1D), semi-classical treatment of the light-induced avoided crossing occurring in the nonadiabatic gas-phase molecular dynamics. Recent studies of the time-dependent state population in the NaI molecule have successfully demonstrated that the 1D results obtained by the semi-classical approach [50] are fully consistent with the results obtained for NaI and quantized light field [24].…”
supporting
confidence: 68%
“…This has been already demonstrated for NaI in previous work [30]. Pure Fock states have the most resemblance with classical light in terms of interaction and dynamics, which has been demonstrated in [33]. In case of a twolevel system their population dynamics are identical (a demonstration is given in Fig.…”
Section: Resultssupporting
confidence: 64%